Pelatihan Metode Cilukba dalam Mencegah Kejadian Stunting pada Balita di Kelurahan Kalebajeng Kecamatan Bajeng Kabupaten Gowa - Muhammad Ikhtiar; Hasriwiani Habo Abbas (PT.Mantaya Idea Batara, 2021)
Stunting or short toddlers are toddlers with chronic nutritional problems, who have nutritional status based on length or height according to the age of toddlers when compared to the standard WHO-MGRS (Multicentre Growth Reference Study) in 2005, has a z-score value of less than -2SD and if the z-score value is less than -3SD categorized as toddler is very short. CILUKBA method training is a method to reduce the incidence of stunting. Cilukba method is kiss, hug and give this intake a method of combining parenting, parenting and nutrition to children. This training model is to train mothers who have children aged 0-5 years to be given knowledge of the right parenting patterns, namely giving kisses and hugs as a sign of affection and emotional closeness between mother and child, so that at the time of feeding the child is getting better, because the child feels comfortable and happy so that the child's growth and development becomes good. The problem faced by partners is cilukba method training has never been done in Kalebajeng Village so it needs to be given about knowledge how to provide parenting, nurturing and providing nutritious intake to toddlers so that their growth and development becomes good and can reduce stunting rates in Kalebajeng Village, Bajeng District, Gowa Regency. The activity will be held for 5 months with funding sources from the UMI Waqf Foundation. The output is in the form of publications in Mass Media (print / electronic), improving the understanding and skills of PKK, KADER and Dasawisma mothers in preventing stunting incidents in toddlers in Kalebajeng Village, Bajeng District, Gowa Regency.